The Awakening within “New Woman” Fiction - Maria-Viorica ARNĂUTU (Annals of Philosophy, Social and Human Disciplines, 2015)
The purpose of this article is to analyze the modernist and feminist aspects of “New Woman” identity and thought entailed by the portrayal of one of Kate Chopinʼs female protagonists: Edna Pontellier. Chopinʼs The Awakening (1899) reflects the authoressʼ regional flavored writing style and her preference for local-color fiction. Kate Chopin was a modernist before her time, but, apart from being a proto-modernist, she is also appreciated for being a proto-feminist. The climax of her female character's feminist awakening and self-liberation is marked by the feast which she prepares in order to celebrate becoming separated from her husband. Within the article, the focus is on critical reception and placing the novel within literary context. Despite the fact that most of her contemporary reviewers accused Chopin of crimes against society, many did have some appreciation for the brilliant and flawless writing that was materialized in an unconventional story which seemed to overshadow the well-governed style of the authoress.